2016
DOI: 10.1016/j.ram.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different polyphenol sources on the efficiency of ellagic acid release by Aspergillus niger

Abstract: Fungal hydrolysis of ellagitannins produces hexahydroxydiphenic acid, which is considered an intermediate molecule in ellagic acid release. Ellagic acid has important and desirable beneficial health properties. The aim of this work was to identify the effect of different sources of ellagitannins on the efficiency of ellagic acid release by Aspergillus niger. Three strains of A. niger (GH1, PSH and HT4) were assessed for ellagic acid release from different polyphenol sources: cranberry, creosote bush, and pomeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…To state briefly, it is a dimeric derivative of gallic acid. EA has numerous health benefits with considerable focus on its pharmacological role and suggested as a rationale lead for drug development (Sepúlveda et al, 2016;Shakeri, Zirak, & F I G U R E 2 Promiscuous molecular targets regulated by EA. All the molecular targets are expanded in the abbreviation section Sahebkar, 2018).…”
Section: Ea and Its Sourcementioning
confidence: 99%
“…To state briefly, it is a dimeric derivative of gallic acid. EA has numerous health benefits with considerable focus on its pharmacological role and suggested as a rationale lead for drug development (Sepúlveda et al, 2016;Shakeri, Zirak, & F I G U R E 2 Promiscuous molecular targets regulated by EA. All the molecular targets are expanded in the abbreviation section Sahebkar, 2018).…”
Section: Ea and Its Sourcementioning
confidence: 99%
“…The obtained extract was decanted and filtered using a filter paper. The filtered solution was passed through Amberlite-XAD16 ® with the conditions described for polyphenols recovery [23] to obtain a powder rich in total polyphenols from L. tridentata (PTP).…”
Section: Extraction Of Polyphenols From Creosote Bushmentioning
confidence: 99%
“…Recently, it was shown the inductive effect of a purified extract of pomegranate ellagitannins in the production of ellagitannase by A. niger under SSF, authors reported an increase in the EAH p (Ascacio-Valdés et al, 2014). The effect of differents sources of polyphenols (cranberry, creosote bush and pomegranate) and fungal strains (A. niger GH1, A. niger HT4 and A. niger PSH) on EA release have been evaluated (Sepúlveda et al, 2016). The best combination was A. niger HT4 on pomegranate peels polyphenols (PP), reaching 350.21 mg g -1 .…”
Section: Ea Production Under Ssf Conditionsmentioning
confidence: 99%